Evaluasi Konfigurasi Spasial pada Fasilitas Umum di Rumah Susun Pekunden Semarang Menggunakan Pendekatan Space Syntax - Hasna Salsabila Mumtaz; Sudarwanto, Budi (Nature : National Academic Journal of Architecture, 2025)
Pekunden Vertical Housing is one of the urban slum upgrading programs initiated by the City of Semarang between 1990 and 1992. As the oldest public housing complex in Semarang, it has experienced significant deterioration and changes in the function of its public facilities over time. These emerging issues need to be evaluated to ensure that Pekunden Vertical Housing can be realigned with its original design objectives—not only as a place of shelter, but also as a space that supports the social and economic needs of its residents. This study aims to apply the space syntax method to evaluate the spatial configuration of public facilities within Pekunden Vertical Housing. A quantitative approach with a spatial focus was adopted, utilizing DepthMapX to analyze connectivity, accessibility, and visibility values. Visibility Graph Analysis (VGA) was selected for its ability to provide insights into how spaces are perceived and accessed from various points within the spatial configuration. The results reveal that the communal spaces within Pekunden Vertical Housing are suboptimal in terms of connectivity, accessibility, and visibility. The public facilities located on the ground floor demonstrate the highest integration values across the complex. In particular, the circulation paths leading to and from Taman Pekunden, as well as the parking area adjacent to Rumah Pintar, have high integration values, making them highly suitable for communal functions and as gathering points for disaster mitigation.